5.2.8 Problems 701 to 800

Table 5.183: Second order linear ODE

#

ODE

Mathematica

Maple

2692

\[ {}y^{\prime \prime }+y = \left \{\begin {array}{cc} t^{2} & 0\le t <1 \\ 0 & 1\le t \end {array}\right . \]

2693

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \left \{\begin {array}{cc} 0 & 0\le t <1 \\ t & 1\le t <2 \\ 0 & 2\le t \end {array}\right . \]

2694

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = \delta \left (t -1\right ) \]

2695

\[ {}y^{\prime \prime }+4 y = \sin \left (t \right )+\delta \left (t -\pi \right ) \]

2696

\[ {}y^{\prime \prime }+y^{\prime }+y = 2 \delta \left (t -1\right )-\delta \left (t -2\right ) \]

2697

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t}+3 \delta \left (t -3\right ) \]

2835

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2836

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2837

\[ {}y^{\prime \prime }-\lambda y = 0 \]

2838

\[ {}y^{\prime \prime }+\lambda y = 0 \]

2839

\[ {}y^{\prime \prime }-2 y^{\prime }+\left (\lambda +1\right ) y = 0 \]

2840

\[ {}y^{\prime \prime }+\lambda y = 0 \]

3059

\[ {}y^{\prime \prime }-4 y = 0 \]

3060

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 0 \]

3061

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 0 \]

3062

\[ {}y^{\prime \prime }-7 y^{\prime }+6 y = 0 \]

3063

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = 0 \]

3064

\[ {}y^{\prime \prime }-2 y^{\prime }-y = 0 \]

3065

\[ {}y^{\prime \prime }-2 y^{\prime }-2 y = 0 \]

3066

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

3067

\[ {}2 y^{\prime \prime }+2 y^{\prime }-y = 0 \]

3088

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

3089

\[ {}y^{\prime \prime } = 0 \]

3100

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = 0 \]

3111

\[ {}y^{\prime \prime }-4 y = 3 \cos \left (x \right ) \]

3112

\[ {}y^{\prime \prime }+y = \sin \left (2 x \right ) \]

3113

\[ {}y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{x} \]

3114

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{-2 x} \]

3115

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

3116

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2} \]

3117

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

3119

\[ {}y^{\prime \prime }-4 y = x +{\mathrm e}^{2 x} \]

3120

\[ {}y^{\prime \prime }-9 y = {\mathrm e}^{3 x}+\sin \left (3 x \right ) \]

3121

\[ {}y^{\prime \prime }-y^{\prime }-6 y = x^{3} \]

3122

\[ {}-2 y^{\prime \prime }+3 y = x \,{\mathrm e}^{x} \]

3123

\[ {}y^{\prime \prime }+4 y = x \sin \left (x \right ) \]

3125

\[ {}y^{\prime \prime }+y^{\prime }+y = {\mathrm e}^{x} \sin \left (3 x \right ) \]

3128

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = x^{3} {\mathrm e}^{2 x} \]

3131

\[ {}y^{\prime \prime }+2 n y^{\prime }+n^{2} y = 5 \cos \left (6 x \right ) \]

3132

\[ {}y^{\prime \prime }+9 y = \left (1+\sin \left (3 x \right )\right ) \cos \left (2 x \right ) \]

3133

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 2 x -{\mathrm e}^{-4 x}+\sin \left (2 x \right ) \]

3135

\[ {}y^{\prime \prime }+4 y = 8 \sin \left (x \right )^{2} \]

3137

\[ {}y^{\prime \prime }-5 y^{\prime }-6 y = {\mathrm e}^{3 x} \]

3138

\[ {}y^{\prime \prime }+4 y = 12 \cos \left (x \right )^{2} \]

3139

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

3140

\[ {}y^{\prime \prime }+y = {\mathrm e}^{x} \sin \left (x \right ) \]

3141

\[ {}2 y^{\prime \prime }+y^{\prime } = 8 \sin \left (2 x \right )+{\mathrm e}^{-x} \]

3142

\[ {}y^{\prime \prime }+y = 3 x \sin \left (x \right ) \]

3143

\[ {}2 y^{\prime \prime }+5 y^{\prime }-3 y = \sin \left (x \right )-8 x \]

3144

\[ {}8 y^{\prime \prime }-y = x \,{\mathrm e}^{-\frac {x}{2}} \]

3145

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

3146

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = {\mathrm e}^{x} \]

3147

\[ {}y^{\prime \prime }+4 y = x^{2} \]

3148

\[ {}y^{\prime \prime }-2 y^{\prime }+y = {\mathrm e}^{2 x} \]

3149

\[ {}y^{\prime \prime }+y = 4 \sin \left (2 x \right ) \]

3150

\[ {}y^{\prime \prime }+4 y = 2 x -2 \sin \left (2 x \right ) \]

3151

\[ {}y^{\prime \prime }-y = 3 x +5 \,{\mathrm e}^{x} \]

3152

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{x}+\sin \left (4 x \right ) \]

3155

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

3156

\[ {}y^{\prime \prime }+a^{2} y = \sec \left (a x \right ) \]

3160

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{\left (1-x \right )^{2}} \]

3161

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sin \left ({\mathrm e}^{-x}\right ) \]

3162

\[ {}y^{\prime \prime }+4 y = \sec \left (x \right ) \tan \left (x \right ) \]

3163

\[ {}y^{\prime \prime }-2 y = {\mathrm e}^{-x} \sin \left (2 x \right ) \]

3164

\[ {}y^{\prime \prime }+9 y = \sec \left (x \right ) \csc \left (x \right ) \]

3165

\[ {}y^{\prime \prime }+9 y = \csc \left (2 x \right ) \]

3166

\[ {}y^{\prime \prime }+y = \tan \left (\frac {x}{3}\right )^{2} \]

3168

\[ {}4 y^{\prime \prime }-4 y^{\prime }+y = {\mathrm e}^{\frac {x}{2}} \ln \left (x \right ) \]

3170

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = {\mathrm e}^{3 x} \]

3172

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = x^{2} \]

3173

\[ {}y^{\prime \prime }+4 y = 2 \,{\mathrm e}^{x} \]

3174

\[ {}y^{\prime \prime }+3 y = 3 \,{\mathrm e}^{-4 x} \]

3175

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{x}}{2}+\frac {{\mathrm e}^{-x}}{2} \]

3176

\[ {}y^{\prime \prime }+y^{\prime }-2 y = {\mathrm e}^{-2 x} \]

3177

\[ {}y^{\prime \prime }+2 y = \sin \left (x \right ) \]

3178

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{3 x}}{2}-\frac {{\mathrm e}^{-3 x}}{2} \]

3179

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = \sin \left (2 x \right ) \]

3180

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

3184

\[ {}y^{\prime \prime }+y = {\mathrm e}^{3 x} \left (1+\sin \left (2 x \right )\right ) \]

3185

\[ {}y^{\prime \prime }+2 n^{2} y^{\prime }+n^{4} y = \sin \left (k x \right ) \]

3186

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = \frac {{\mathrm e}^{x}}{2}+\frac {{\mathrm e}^{-x}}{2} \]

3187

\[ {}y^{\prime \prime }+y^{\prime }-2 y = x \,{\mathrm e}^{-x} \]

3188

\[ {}y^{\prime \prime }+4 y = x \,{\mathrm e}^{x} \]

3189

\[ {}y^{\prime \prime }+2 y = x^{2} {\mathrm e}^{-x} \]

3190

\[ {}y^{\prime \prime }-y^{\prime }-2 y = x^{2}-8 \]

3205

\[ {}y^{\prime \prime }+4 y = x \sin \left (x \right ) \]

3206

\[ {}y^{\prime \prime }+y = x^{2} \cos \left (x \right ) \]

3207

\[ {}y^{\prime \prime }-y = x^{2} \cos \left (x \right ) \]

3210

\[ {}2 y^{\prime \prime }+3 y^{\prime }-2 y = {\mathrm e}^{x} x^{2} \]

3214

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = x^{2} \cos \left (x \right ) \]

3215

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = x^{2} \sin \left (x \right ) \]

3216

\[ {}y^{\prime \prime }-y = \sin \left (2 x \right ) x \]

3217

\[ {}y^{\prime \prime }+2 y^{\prime } = x^{3} \sin \left (2 x \right ) \]

3218

\[ {}y^{\prime \prime }-y^{\prime } = x \,{\mathrm e}^{2 x} \sin \left (x \right ) \]

3219

\[ {}y^{\prime \prime }-4 y = x \,{\mathrm e}^{2 x} \cos \left (x \right ) \]

3220

\[ {}y^{\prime \prime }+2 y^{\prime } = x^{2} {\mathrm e}^{-x} \sin \left (x \right ) \]

3221

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+y = 0 \]

3222

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+16 y = 0 \]

3223

\[ {}4 x^{2} y^{\prime \prime }-16 x y^{\prime }+25 y = 0 \]

3224

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+10 y = 0 \]